Dopamine-mediated improvements of the step threshold task in Parkinson’s disease: validation against clinical measures of motor and cognitive function - Moll, Alyson N.; Walker, Harrison C.; Rosenblatt, Noah; Kuhman, Daniel J.; Adams, Jaden; Del Bene, Victor A.; Martin, Roy C.; Brinkerhoff, Sarah; Hurt, Christopher P. (Frontiers in Human Neuroscience, 2025)
IntroductionStandardized treadmill-based balance disturbances have potential to improve assessments of dynamic balance control in individuals with Parkinson’s disease. Here we examined the validity of a step threshold task to measure dynamic balance control in patients with Parkinson’s disease.MethodsThirty-nine participants with idiopathic Parkinson’s disease underwent clinical testing and performed a dynamic balance assessment both OFF and ON dopaminergic medication. For the assessment, participants were instructed to avoid stepping in response to progressively larger postural perturbations applied via treadmill translations. The step threshold was defined as the perturbation magnitude that resulted in a stepping response on four consecutive trials. Validity was assessed by correlating medication-mediated changes in gold standard clinical measures and medication-mediated changes in stepping.ResultsMedication-mediated changes in step threshold correlated with changes in MDS-UPDRS part III (p < 0.01), with change in MDS-UPDRS 3.12 postural instability (p < 0.05), and with measures of executive function: CPT-3 Omission T-score (p = 0.013), the CPT-3 Commission T-score (p = 0.019), and the CPT-3 Variability T-score (p = 0.040).DiscussionOur results validate step threshold task as a measure of dynamic balance control in patients with Parkinson’s disease. Correlations with gold standard assessments of motor and executive function suggest that the step threshold task can serve as a comprehensive measure of dynamic balance control.